The utilization of NDCP (natural defluorinated calcium phosphate) in broiler ration as compared with dicalcium phosphate - Sinurat, A.P.; Dharsana, R.; Pasaribu, T.; Panggabean, T.; Habibie, A. (Indonesian Journal of Animal and Veterinary Sciences, 1995)
An experiment was conducted to study the utilization of local rock phosphate or natural defluorirutted calcium phosphate (NDCP) as phosphorus source for broilers by using the imported dicalcium phosphate (DCP) as a reference . The study was designed by formulating 6 experimental diets which consist of 2 phosphorus sources (DCP dan NDCP) and 3 dietary total P levels (0 .55 ; 0.65 and 0 .75%) . Each diet was fed to 60 chickens (10 replicates with 6 birds each) from three day old to 6 weeks of age . Parameters observed were feed consumption, body weight gain, mortality, Ca and P retention, and ash content of tibia bones . Results showed that dietary phosphorus levels (0 .55 to 0 .75 %) did not significantly affect body weight gain, feed consumption, and mortalities . However, better feed conversion ratio was obtained when dietary phosphorus level was 0 .55% . The NDCP treated birds could significantly gain heavier weight compared with those received DCP, although this improvement was also followed by an increase in the feed consumption . The relative biological value of phosphorus in NDCP was 101 `7n . It is concluded that NDCP can he used in broilers diet to replace DCP as phosphorus source . Key words : Rock phosphate, NDCP, broiler